Spline and Spline Wavelet Methods with Applications to Signal and Image Processing Volume II: Non-Periodic Splines - Averbuch, Amir Z.; Neittaanmäki, Pekka; Zheludev, Valery A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents various contributions of splines to signal and image processing from a unified perspective that is based on the Zak transform (ZT). It expands the methodology from periodic splines, which were presented in the first volume, to non-periodic splines. Together, these books provide a universal toolbox accompanied by MATLAB software for manipulating polynomial and discrete splines, spline-based wavelets, wavelet packets and wavelet frames for signal/ image processing applications. In this volume, we see that the ZT provides an integral representation of discrete and polynomial splines, which, to some extent, is similar to Fourier integral. The authors explore elements of spline theory and design, and consider different types of polynomial and discrete splines. They describe applications of spline-based wavelets to data compression. These splines are useful for real-time signal processing and, in particular, real-time wavelet and frame transforms. Furthertopics addressed in this volume include: "global" splines, such as interpolating, self-dual and smoothing, whose supports are infinite; the compactly supported quasi-interpolating and smoothing splines including quasi-interpolating splines on non-uniform grids; and cubic Hermite splines as a source for the design of multiwavelets and multiwavelet frames. Readers from various disciplines including engineering, computer science and mathematical information technology will find the descriptions of algorithms, applications and software in this book especially useful.
Preface.-1 Introduction: Signals and Transforms -- 2 Introduction: Digital Filters and Filter Banks -- 3 Mixed Convolutions and Zak Transforms -- 4 Non-Periodic Polynomial Splines -- 5 Quasi-Interpolating and Smoothing Local Splines -- 6 Cubic Local Splines on Non-Uniform Grid -- 7 Splines Computation by Subdivision -- 8 Polynomial Spline-Wavelets -- 9 Non-Periodic Discrete Splines -- 10 Non-Periodic Discrete-Spline Wavelets -- 11 Biorthogonal Wavelet Transforms -- 12 Biorthogonal Wavelet Transforms Originating from Splines -- 13 Data Compression Using Wavelet and Local Cosine Transforms -- 14 Wavelet Frames Generated by Perfect Reconstruction Filter Banks -- 15 Biorthogonal Multiwavelets Originated from Hermite Splines -- 16 Multiwavelet Frames Originated from Hermite Splines -- Appendix A - Guide to Spline SoftN -- Glossary -- Index.
Keywords: Signal processing; Image processing -- Digital techniques; Computer vision; Mathematics -- Data processing; Signal, Speech and Image Processing; Computer Imaging, Vision, Pattern Recognition and Graphics; Computational Mathematics and Numerical Analysis